Female and male fitness of a sexually deceptive orchid with a narrow distribution area: from phenotypic traits to spatial distribution patterns. (3rd November 2020) - Borràs, J.; Cursach, J.
Abstract: The Orchidaceae family presents one of the most extravagant pollination mechanisms: deception. While many studies on reproductive success have been performed on food‐deception orchids, less have been performed on sexually deceptive orchids. Here, we focused on Ophrys balearica P. Delforge, an endemic orchid of the Balearic Islands, to study its reproductive ecology, the spatio‐temporal variation of its reproductive success and the individual (floral display and geospatial position) and population parameters (patch size, shape and density) that affect its reproductive success. We performed hand‐pollination experiments, along with the recording of floral display parameters and GPS position of over 1, 100 individuals from seven populations in two consecutive years. We applied, for the first time, GIS tools to analyse the effects of individual's position within the population on the reproductive success. Reproductive success was measured both in male (removed pollinia) and female (fruit set) fitness. The results confirm that this species is pollinator‐dependent and mostly allogamous, but also self‐compatible. This species showed high values for the cumulative inbreeding depression index and high pollen limitation. Male fitness was almost equal to female fitness between years and populations, and reproductive success exhibited huge spatio‐temporal variation. Although we did not find strong correlations between floral display and reproductive success, patches with low‐plant density and individuals in the external portion of the population showed significantly higher plant fitness. These findings must be considered in conservation actions for endangered orchid species, especially considering that most orchids are strongly dependent on pollinators for their species' fitness. Abstract : Population parameters (individual density and position) influence more than individual (biometric) parameters on the reproductive success of a sexual deceptive orchid.